# Calculus

Differentiation of Functions# Basic Differentiation Rules

Problems 1-3

Problems 4-10

The operation of differentiation or finding the derivative of a function has the fundamental property of linearity. This property makes taking the derivative easier for functions constructed from the basic elementary functions using the operations of addition and multiplication by a constant number. The basic differentiation rules allow us to compute the derivatives of such functions without using the formal definition of the derivative. Consider these rules in more detail.

### Derivative of a Constant

If \(f\left( x \right) = C\), then

The proof of this rule is considered on the Definition of the derivative page.

### Constant Multiple Rule

Let \(k\) be a constant. If \(f\left( x \right)\) is differentiable, then \(kf\left( x \right)\) is also differentiable and

### Sum Rule

Let \(f\left( x \right)\) and \(g\left( x \right)\) be differentiable functions. Then the sum of two functions is also differentiable and

Let \(n\) functions \({f_1}\left( x \right)\), \({f_2}\left( x \right)\), \(\ldots\), \({f_n}\left( x \right)\) be differentiable. Then their sum is also differentiable and

{{\left[ {{f_1}\left( x \right) + {f_2}\left( x \right) + \ldots + {f_n}\left( x \right)} \right]^\prime } }

= {{f_1}^\prime \left( x \right) + {f_2}^\prime \left( x \right) + \ldots + {f_n}^\prime \left( x \right).}

\]

Combining the both rules we see that the derivative of difference of two functions is equal to the difference of the derivatives of these functions assuming both of the functions are differentiable:

We can write the common rule:

### Linear Combination Rule

Suppose \(f\left( x \right)\) and \(g\left( x \right)\) are differentiable functions and \(a,\) \(b\) are real numbers. Then the function \(h\left( x \right) = af\left( x \right) + bg\left( x \right)\) is also differentiable and

We add to this list one more simple rule:

### Derivative of the Function \(y = x\)

If \(f\left( x \right) = x,\) then

This formula is derived on the Definition of the derivative page.

## Solved Problems

Click on problem description to see solution.

### ✓ Example 1

Find the derivative of the function \(y = {x^2} – 5x\).

### ✓ Example 2

Find the derivative of the function \(y = {\large\frac{{ax + b}}{{a + b}}\normalsize}\), where \(a\) and \(b\) are constants.

### ✓ Example 3

Find the derivative of the function \(y = 2\sqrt x – 3\sin x\).

### ✓ Example 4

Calculate the derivative of the function \(y = 3\sin x + 2\cos x\).

### ✓ Example 5

Let \(y = x + \left| {{x^2} – 8} \right|\). Find the derivative of the function at \(x = 3\).

### ✓ Example 6

Find the derivative of the function \(y = {\large\frac{2}{{3x}}\normalsize} + 3{x^4}\).

### ✓ Example 7

Find the derivative of the function \(y = \sqrt[3]{x} + 8x\).

### ✓ Example 8

Calculate the derivative of the function \(y = \left( {2 – {\large\frac{x}{3}\normalsize}} \right)\left( {{\large\frac{1}{3}\normalsize} + {x^2}} \right)\).

### ✓ Example 9

Calculate the derivative of the function \(y = \left( {x – 1} \right){\left( {x – 2} \right)^2}\) without using the product rule for the derivative.

### ✓ Example 10

Find the derivative of the function \(y = {\large\frac{{{x^2} + 3x + 1}}{x}\normalsize}\) without using the quotient rule for the derivative.

### Example 1.

Find the derivative of the function \(y = {x^2} – 5x\).

*Solution.*

Using the linear differentiation rules, we have

{y’\left( x \right) = {\left( {{x^2} – 5x} \right)^\prime } }

= {{\left( {{x^2}} \right)^\prime } – {\left( {5x} \right)^\prime } }

= {{\left( {{x^2}} \right)^\prime } – 5{\left( x \right)^\prime } }

= {2x – 5 \cdot 1 = 2x – 5.}

\]

### Example 2.

Find the derivative of the function \(y = {\large\frac{{ax + b}}{{a + b}}\normalsize}\), where \(a\) and \(b\) are constants.

*Solution.*

{y’\left( x \right) = {\left( {\frac{{ax + b}}{{a + b}}} \right)^\prime } }

= {\frac{1}{{a + b}} \cdot {\left( {ax + b} \right)^\prime } = {\frac{a}{{a + b}}.}}

\]

### Example 3.

Find the derivative of the function \(y = 2\sqrt x – 3\sin x\).

*Solution.*

Using the basic differentiation rules, we obtain:

{y’\left( x \right) = {\left( {2\sqrt x – 3\sin x} \right)^\prime } }

= {{\left( {2\sqrt x } \right)^\prime } – {\left( {3\sin x} \right)^\prime } }

= {2{\left( {\sqrt x } \right)^\prime } – 3{\left( {\sin x} \right)^\prime } }

= {2 \cdot \frac{1}{{2\sqrt x }} – 3\cos x }

= {\frac{1}{{\sqrt x }} – 3\cos x.}

\]

Problems 1-3

Problems 4-10